Pathways of Glucagon Secretion and Trafficking in the Pancreatic Alpha Cell: Novel Pathways, Proteins, and Targets for Hyperglucagonemia - Asadi, Farzad; Dhanvantari, Savita (Frontiers in Endocrinology, 2021)
Patients with diabetes mellitus exhibit hyperglucagonemia, or excess glucagon secretion, which may be the underlying cause of the hyperglycemia of diabetes. Defective alpha cell secretory responses to glucose and paracrine effectors in both Type 1 and Type 2 diabetes may drive the development of hyperglucagonemia. Therefore, uncovering the mechanisms that regulate glucagon secretion from the pancreatic alpha cell is critical for developing treatments for hyperglucagonemia. In this review, we focus on aspects of alpha cell biology for possible mechanisms for hyperglucagonemia in diabetes: proglucagon processing, intrinsic and paracrine control of glucagon secretion, secretory granule dynamics, and alterations in intracellular trafficking. We explore possible clues gleaned from these studies in how inhibition of glucagon secretion can be targeted as a treatment for diabetes mellitus.